AMAN Indonesia's Contribution To Voicing The Peace Of Muslim Women In Indonesia by Using Social Media - Syahriyah, Ummi Ulfatus; Yulianti, Yulianti; Zein, Muhammad Khafid Zulfahmi; Dwiriani, Vera (AL-WIJDÃN Journal of Islamic Education Studies, 2023)
The diversity that exists in Indonesia creates harmony but also creates conflict. In resolving a conflict, discussions must be held in order to create peace. Peace in resolving a conflict is not only carried out by men but women also have a very large role in voicing peace. With the development of technology and information media, peace campaigns can be carried out using social media but must be carried out by institutions that have been systematically organized so that peace goals can be achieved. The purpose of this study is to see the contribution of AMAN Indonesia as Indonesia's largest women's institution in voicing the peace of Muslim women in Indonesia using social media. The research method in this study uses descriptive qualitative using literature studies. The results of this study show that an institutional contribution to voicing women can be done with organized and transformed social movements using new technologies such as social media. AMAN Indonesia as a well-organized organization uses social media as a tool in voicing the peace of Muslim women in Indonesia. The activities carried out by AMAN Indonesia in voicing the peace of Muslim women in Indonesia are conducting open dialogues, group discussions, watching peaceful films, and education on social media.   Keywords: Muslim Women, Peace, Social Media, AMAN Indonesia